2016
DOI: 10.1007/s00223-016-0186-7
|View full text |Cite
|
Sign up to set email alerts
|

Bone Mineral Density and Body Composition are Associated with Circulating Angiogenic Factors in Post-menopausal Women

Abstract: Lean mass (LM) and fat mass (FM) are closely related to bone mass (BM) in post-menopausal women, although their relative importance is unclear. Angiogenic factors which control angiogenesis may influence BM, LM and FM. The aim of the study was to compare the contribution of LM and FM to bone mineral density (BMD) and the association between these tissues and circulating angiogenic factors. The study population comprised of 392 post-menopausal women aged mean [SD] 61.8 [6.4] years. BMD was measured at the lumba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…According to the International Osteoporosis Foundation, more than 200 million people suffer from this disease worldwide 5. Recent studies suggest that there are two main issues to be solved in osteoporosis; one is increased osteoclastic bone resorption, and the other is decreased angiogenesis 6. Nevertheless, the current first line antiresorptive drug bisphosphonate only solves the first problem which is increased osteoclastogenesis but left the second problem behind.…”
Section: Introductionmentioning
confidence: 99%
“…According to the International Osteoporosis Foundation, more than 200 million people suffer from this disease worldwide 5. Recent studies suggest that there are two main issues to be solved in osteoporosis; one is increased osteoclastic bone resorption, and the other is decreased angiogenesis 6. Nevertheless, the current first line antiresorptive drug bisphosphonate only solves the first problem which is increased osteoclastogenesis but left the second problem behind.…”
Section: Introductionmentioning
confidence: 99%
“…Most studies suggest that the changes in the composition of the female body coincide with menopause. Some of these changes can be partly explained by the impairment of the protective role of estrogens and a relative increase in circulating androgen levels [14]. Previous studies have demonstrated that endogenous sex hormones can influence the lipid profile in premenopausal and postmenopausal women because the receptors for estrogen and androgen are expressed in both visceral and subcutaneous adipocytes.…”
Section: Menopause-associated Changes In Fat Mass and Fatty Acid Metabolismmentioning
confidence: 99%
“…In this study, we tested the hypothesis of whether endothelial dysfunction, diagnosed on the basis of increased blood sVCAM-1 concentration, affects AF occurrence and patient prognosis (risk of all-cause mortality, readmission, or stroke). We did so because endothelial dysfunction is related to the risk of several cardiovascular diseases [3], to the presence of inflammation [12], to obesity and body composition [9,[13][14][15][16][17][18][19], as well as being involved in the risk of thromboembolic complications of AF [20][21][22][23][24]. We also investigated whether sVCAM-1 might link obesity with the pathogenesis of AF and patient prognosis [10,11].…”
Section: Discussionmentioning
confidence: 99%
“…Blood sVCAM-1 concentration was analyzed as a crude value and as a ratio to the following: blood C-reactive protein (CRP) concentration, fat mass (FM), and visceral adipose tissue (VAT). The rationale for such indexation of sVCAM-1 was that its secretion and serum concentration are related to the presence of inflammation (CRP, inflammation related to obesity and fat mass) [12], obesity and body composition (FM, VAT) [9,[13][14][15][16][17][18][19]. In this way, we can compare sVCAM-1 level adjusted to interpersonal diversity in inflammatory and adiposity status.…”
Section: Parameters Of Nutritional Status Assessmentmentioning
confidence: 99%
See 1 more Smart Citation